2006
DOI: 10.1111/j.1468-0084.2006.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Training on Productivity and Wages: Evidence from British Panel Data*

Abstract: It is standard in the literature on training to use wages as a sufficient statistic for productivity. This paper examines the effects of work-related training on direct measures of productivity. Using a new panel of British industries 1983-1996 and a variety of estimation techniques we find that work-related training is associated with significantly higher productivity. A one percentage point increase in training is associated with an increase in value added per hour of about 0.6% and an increase in hourly wag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
296
4
14

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 379 publications
(337 citation statements)
references
References 51 publications
13
296
4
14
Order By: Relevance
“…This finding is somewhat different from most previous literature that compares the effects of training on firms and workers (Conti 2005;Ballot et al 2006;Dearden et al 2006) that has found stronger evidence of positive effects on organizational performance rather than on wages.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…This finding is somewhat different from most previous literature that compares the effects of training on firms and workers (Conti 2005;Ballot et al 2006;Dearden et al 2006) that has found stronger evidence of positive effects on organizational performance rather than on wages.…”
Section: Discussioncontrasting
confidence: 56%
“…This applies both to industry levels studies (Conti 2005;Dearden et al 2006) and firm level studies (e.g. Ballot et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the financial strength of the firm leads to productivity improvement (Dearden et al, 2006). To control for this issue, we used information on firms' earnings before interest, taxes, and depreciation.…”
Section: Earningsmentioning
confidence: 99%
“…Our estimated coefficients on the other hand indicate that an improvement by one health category increases wages by 7%. Previous findings on the relationship between on-the-job-training and wages by Dearden et al (2006) show that a 1% point increase in training is associated with an increase in hourly wages of about 0.3%. Parameter values for our development accounting exercise are based on estimated coefficients from our preferred specification, see Table 4.…”
Section: Parametrizationmentioning
confidence: 99%